A Sustainable Model for Business Schools? - PETERS, Kai (Institutional Knowledge at Singapore Management University, 2011)
The article looks at the condition of business model of business schools, and presents the views of the authors on its instability in terms of finance and unsustainability. It explores the financial drivers of business schools, both on the income and expenditure sides, as well as highlights the areas of distinct concern for business school finances. The sources of funding for business schools are discussed.